Teenage Tata : voices of young fathers in South Africa - Swartz, Sharlene; Bhana, Arvin (Cape Town, South Africa : HSRC Press, 2009)
Teenage Tata provides a fresh and in-depth portrait of impoverished young South African men who became fathers while teenagers. It provides space for their articulate and impassioned voices to be heard amidst t he outcry against the absence of fathers, and offers insights into youn g fathers' personal, emotional, financial and cultural struggles as the y come to terms with fatherhood. The study highlights young fathers' st rong sense of responsibility; poignant accounts of emotional engagement with their children and the women in their lives; the motivating power of young fathers' own absent fathers on their parenting intentions; th eir desire for sex-and relationship-education from male family members and their clear recognition of the help they need. Based on a multi-int erview qualitative study in the informal settlements and townships arou nd Cape Town and Durban, this monograph offers methodological innovatio ns and showcases how social network interviews offer great potential fo r both research and intervention.
Includes bibliographical references.
Keywords: Teenage fathers; Teenage parents